(untitled) (Scientific journal of the Fergana State University, 2023)
Based on historical sources, this article reveals the main provisions of the implementation of industrialization policies in the Khashkadarya region in the 40–80s of the XX century. Based on the analysis, it was revealed and described that the production products served the interests of the former union, and not the region (republic), therefore, industrial enterprises were very close to cities and to each other. As a result of the careless use of the material and technical base of industrial enterprises and for the rapid achievement of results, as well as due to the discharge of waste into the environment, environmental damage was caused.